Book Review “Drive – The Surprising Truth About What Motivates Us”, by Daniel H. Pink - Landau, Heinz (ABAC ODI JOURNAL Vision. Action. Outcome, 2015)
The Author Daniel H. Pink is the author of several provocative, bestselling books about business, work, and behaviour. His books have been translated into 34 languages and have sold more than two million copies. Before venturing out on his own, Pink worked in several positions in politics and government. He served as chief speechwriter to U.S. Vice President Al Gore. Pink is a frequent contributor to business magazines in the U.S. and a business trend analyst for several U.S. TV stations. In “Drive”, he reveals the three elements of true motivation: Autonomy – the desire to direct our own lives Mastery – the urge to get better at something that matters Purpose – the yearning to do what we do in the service of something larger than ourselves In 2013, Thinkers 50 named Pink one of the top 15 business thinkers in the world.